Detection of Haemophilus Parasuis from The Respiratory Tract of Pigs - Suarjana, I Gusti Ketut; Besung, I Nengah Kerta; Tono PG, Ketut (Journal of Veterinary and Animal Sciences; Vol 1 No 1 (2017)DO - 10.24843/JVAS.2017.v01.i01.p03, 2017)
Study in order to detect the presence of Haemophilus parasuis in pig farms in Tabanan, Badung, and Gianyar Bali have been undertaken. A total of 197samples including nasal and tracheal swabs, organs and synovial fluids were collected from 69, 28 and 100 animals from pig farms in Tabanan, Badung and Gianyar regency, respectively. Samples were collected mainly from animals which showing clinical signs of coughing, asphyxiate, swollen joints and death animals. Isolation and identification of Haemophilus spp was performed following the methods described by Priadi et.al. (2004) and Nedbalkova et al. (2006) with slightly modification. Antimicrobial sensitivity test was performed using the disc diffusion method by Kirby Bauer.Haemophilus parasuis was detected from one sample which shown resistant to streptomycin only and sensitive to ampicillin, doxycycline and kanamycin, respectively.